DEVELOPMENT OF UNDERARM PASSING IN VOLLEYBALL THROUGH TRADITIONAL GAME APPROACH - Aep Rohendi; james Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2015)
This research is aimed to develop a model of underarm passing involleyball through traditional game’s basic movement approach. The methodused for this learning method development is Research and Development (R &D) Development Method. By choosing SMPN III Parongpong in West BandungRegency as the location of this study, this study is done through 8 stages: first,determining idea to develop; second, producing a design; third, evaluating,improving and completing the text; forth, revising a product by the expert; fifth, aprototype product done by taking product picture; sixth, prototype test, the testof subject field both in stage I and stage II test; seventh, revising a secondproduct of which revision was done by an expert; eighth, producting a completeto be the final product. From those stages, the result of the study is gained byfirst stage evaluation analysis of ten products. The total respondent score isresulted with data number = 123. Therefore, effectiveness of new teachingmethod in total = 123 : 144= 0,85 or 85% from the expected criteria and basedon stage II evaluation analysis by using numbered final product, the totalrespondent score is resulted with data number = 246. Therefore, the totaleffectiveness of teaching method = 246 : 288 = 0,85 or 85% from the expectedcriteria to fulfill valid criteria. Based on the result of the study, it can beconcluded that: (1) Underarm passing learning model in volleyball through gatriktraditional game approach in SMPN 3 Parongpong is needed by PhysicalEducation teachers and improving the learning process of underarm passingeffectively and efficiently. (2) Application of the developed learning model willmake students more motivated in joining learning process. Key Words: Model development, underarm passing, traditional gameapproach